Water induced sediment levitation enhances downslope transport on Mars. Issue 1 (December 2017) - Raack, Jan; Conway, Susan; Herny, Clémence; Balme, Matthew; Carpy, Sabrina; Patel, Manish
Abstract On Mars, locally warm surface temperatures (~293 K) occur, leading to the possibility of (transient) liquid water on the surface. However, water exposed to the martian atmosphere will boil, and the sediment transport capacity of such unstable water is not well understood. Here, we present laboratory studies of a newly recognized transport mechanism: "levitation" of saturated sediment bodies on a cushion of vapor released by boiling. Sediment transport where this mechanism is active is about nine times greater than without this effect, reducing the amount of water required to transport comparable sediment volumes by nearly an order of magnitude. Our calculations show that the effect of levitation could persist up to ~48 times longer under reduced martian gravity. Sediment levitation must therefore be considered when evaluating the formation of recent and present-day martian mass wasting features, as much less water may be required to form such features than previously thought. Downslope sediment transport on Mars is reported, but the transport capacity of unstable water under low pressures is not well understood. Here, the authors present a newly discovered, highly reactive transportation mechanism that is only possible under low pressure environments.